(untitled) (Maryland Heights, Mo., 2014)
Written by the foremost experts in maternity and pediatric nursing, Maternal Child Nursing Care, 5th Edition offers the accurate, practical information you need to succeed in the classroom, the clinical setting, and on the NCLEX® examination. This new edition offers numerous content updates throughout the text to keep you up-to-date on the latest topics and best practices. Plus hundreds of illustrations, alert boxes, and tables clarify key content and help you quickly find essential information.
Keywords: Pediatric nursing,Maternal-Child Nursing,Điều dưỡng thai sản,Điều dưỡng nhi,Điều dưỡng bà mẹ - trẻ em,Maternity nursing